Problems of laser beam width measuring with CCD cameras - Dementjev, Aleksandr; Ivanauskas, Feliksas; Vaicekauskas, Rimantas; Radavičius, Marijus (Lietuvos matematikos rinkinys, 1997)
There is not abstract.